Depression, Anxiety, Stress, and Their Associations With Quality of Life in a Nationwide Sample of Psychiatrists in China During the COVID-19 Pandemic - Li, Mengdie; Xia, Lei; Yang, Yating; Zhang, Ling; Zhang, Shujing; Liu, Tingfang; Liu, Yuanli; Kaslow, Nadine J.; Jiang, Feng; Tang, Yi-lang; Liu, Huanzhong (Frontiers in Psychology, 2022)
Objectives The COVID-19 pandemic has negatively affected wellbeing. However, the impact on the mental health status of Chinese psychiatrists and their relationship with quality of life (QOL) has not been examined. Methods This was a national cross-sectional survey performed between January 11 and March 15, 2021. Demographic and work-related data were collected anonymously using an online questionnaire. Common mental health symptoms and QOL were assessed using the Depression Anxiety Stress Scale-Chinese version and the World Health Organization Quality of Life Schedule-Brief, respectively. Results A total of 3,783 psychiatrists completed this questionnaire. The prevalence of depressive, anxious, and stress symptoms were 26.7% (95%CI = 25.3–28.1%), 24.1% (95%CI = 22.8–25.5%), and 11.6% (95%CI = 10–12%), respectively. Moreover, 11.1% of the participants endorsed both depressive and anxious symptoms, and 8% endorsed symptoms in all three domains. Binary logistic regression showed that aged 30–39 years (OR = 1.5, P = 0.03), male gender (OR = 1.2, P = 0.04), single (OR = 1.44, P = 0.01), and having a negative perception of the COVID-19 on healthcare (OR = 2.34, P <0.001) were factors associated with higher levels of depressive symptoms. Participants who were divorced and widowed (OR = 1.56, P = 0.03), worked more than 4 night shifts/month (OR = 1.33, P<0.001) and/or longer working years (OR = 1.71, P < 0.001), and had a negative perceived impact of the COVID-19 on healthcare (OR = 2.05, P < 0.001) were more inclined to experience anxious symptoms. In addition, psychiatrists with high QOL scores had lower odds of experiencing depressive, anxious, and stress symptoms (all P < 0.001). Multivariate analysis showed that the presence of each of the three types of mental health symptoms was independently associated with lower QOL (all P < 0.05). In addition, the depression × anxious × stress interaction was significantly correlated with lower QOL (P < 0.05). Conclusion Approximately one-fourth of psychiatrists in China experienced depressive and anxious symptoms during the COVID-19 pandemic, and more than one-tenth reported stress. Mental health symptoms were significant contributors to lower QOL. The psychological wellbeing of psychiatrists during the pandemic requires more attention, and interventions are needed to improve the psychological wellbeing and QOL of physicians who care for individuals with mental disorders.